Between-species differences in gene copy number are enriched among functions critical for adaptive evolution in Arabidopsis halleri - Suryawanshi, Vasantika; Eils, Roland; Krämer, Ute (BMC genomics, 2016)
Gene copy number divergence between species is a form of genetic polymorphism that contributes significantly to both genome size and phenotypic variation. In plants, copy number expansions of single genes were implicated in cultivar- or species-specific tolerance of high levels of soil boron, aluminium or calamine-type heavy metals, respectively. Arabidopsis halleri is a zinc- and cadmium-hyperaccumulating extremophile species capable of growing on heavy-metal contaminated, toxic soils. In contrast, its non-accumulating sister species A. lyrata and the closely related reference model species A. thaliana exhibit merely basal metal tolerance.